The effect of acrylamide on the peripheral nervous system of the baboon. Issue 6 (December 1970) - Hopkins, Anthony
Abstract : In the baboon, acrylamide produces a clinical illness characterized by weakness and ataxia of the limbs, weakness of bulbar muscles, and finally tetraplegia. Histological examination shows extensive involvement of peripheral nerves, the main histological change being a Wallerian type of degeneration affecting the distal ends of the largest diameter nerve fibres. The phenomenon of `dying back' has been demonstrated in single teased fibres. Changes also occur in the paranodal myelin; these are not necessarily associated with degeneration of the axon, since intercalated segments and extension of myelin from neighbouring internodes are present in recovering animals. Demyelination of whole internodes is rare. Paranodal changes may be found a few millimetres proximal to complete degeneration, but may also occur on fibres which are otherwise normal in the length examined. The mechanism of the paranodal changes is uncertain, but they may indicate a secondary response of the Schwann cell to a primary change in the axon.